Inhibition of herpes simplex virus type 1 DNA polymerase activity by peptides from the UL42 accessory protein is largely nonspecific. - Owsianka, A M (1993)
To identify regions in the UL42 protein of herpes simplex virus type 1 which affect viral DNA polymerase activity, a series of 96 overlapping pentadecapeptides spanning the entire 488 amino acids of the UL42 protein were synthesized and tested for their ability to inhibit polymerase activity on a primed single-stranded M13 DNA template. Two assays were used: formation of full-length double-stranded M13 molecules and rate of incorporation of deoxyribonucleoside triphosphates. Peptides from five noncontiguous regions of the UL42 protein were found to inhibit herpes simplex virus type 1 polymerase activity in both the presence and absence of UL42 protein. The most active peptides from each region correspond to amino acids 23 to 38 (peptide 6), 64 to 78 (peptide 14), 89 to 102 (peptide 19), 229 to 243 (peptide 47), and 279 to 293 (peptide 57). By two different methods (DNA mobility shift and DNA precipitation), peptides 14, 19, 47, and 57 were found to bind DNA; they most probably inhibit enzyme activity by this mechanism. Peptide 6 did not bind DNA and must act by some mechanism other than competing for DNA. The inhibitory peptides were also tested for activity against mammalian polymerase alpha and the Klenow fragment of Escherichia coli polymerase. Although some limited specificity was demonstrated (up to 10-fold for peptide 6), all the peptides showed significant activity against both polymerase alpha and E. coli polymerase.